Banyumasan Cultural Values Implication for Character Education (Perspective of Prophetic Epistemology) - Maulana Zakiyah, Ita (International Proceedings of Nusantara Raya, 2024)
The erosion of local cultural values in character education in Indonesia is increasingly visible, the influence of globalization brings many polemics such as modernization and outside cultural influences. This is one of the factors that threaten the preservation of the cultural value of Banyumasan. The existence of challenges to maintain the cultural value of Banyumasan which plays a role in the formation of character, this study is important to be studied in the midst of the Times. The purpose of this study is to analyze the cultural value of Banyumasan in the perspective of prophetic epistemology in order to apply it to the development of character education. This type of research is qualitative with literature study methods taken from various literature sources such as journals, books, documents, and others. Data collection was conducted by interviews, observations, and documentation studies on Banyumasan cultural values relevant to character education using a prophetic epistimology approach. The results of this study that Banyumasan cultural values such as sabar lan nrimo, jiwa ksatria, cacundan, cablaka can help improve the process of student character formation so as to maintain the local cultural identity of Banyumasan.